Transformation of Rucah Fish Processing Into Nuggets in Setapuk Besar Village Singkawang City - Sukal Minsas; Warsidah Warsidah; Mega Sari Juane Sofiana; Yusuf Arief Nurrahman; Arie Antasarie Kushadiwijayanto; Dwi Imam Prayitno; Sy Irwan Nurdiansyah (STKIP Singkawang, 2022)
Fish nugget is a type of fishery product processing that has a long shelf life at cold or frozen temperatures. The presentation is more practical, tastes more savory and is liked by children and adolescents, so it can be used to meet the nutritional needs of the family. The implementation of this PKM activity aims to provide training to the people of Setapuk Besar, Singkawang City, in processing trash fish fisheries waste into nuggets, with the addition of Eucheuma cottonii pulp as a partial substitute for wheat flour. This activity is carried out offline while still paying attention to and strictly implementing health protocols such as wearing masks and using hand sanitizers. The activity was attended by 20 participants consisting of members of the Setapuk Besar Village Family Welfare Development (PKK) divided into 3 working groups. This PKM activity was carried out using the lecture method followed by a demonstration of making nuggets. Monitoring and evaluation of the activities carried out during the activity showed the ability of the 3 groups of PKK mothers to process trash fish waste into frozen food nuggets based on variations in the concentration of 0, 25 and 50 g E. cottoni pulp. The results of the nugget-making activity for PKK women in Setapuk Besar village, showed that the addition of 0.25 g of E. cottoni pulp provided a better consistency of the dough and texture of processed nuggets, as well as a more savory taste.